Risk of Venous Thromboembolism in Patients with Inflammatory Bowel Disease - Koutroumpakis, Efstratios I.; Tsiolakidou, Georgia; Koutroubakis, Ioannis E. (Seminars in Thrombosis and Hemostasis, 2013)
There is ample evidence of an increased risk of venous thromboembolism (VTE) in inflammatory bowel disease (IBD). Recent large studies have quantified this risk showing that IBD patients run a 1.5 to 3.6 higher risk of developing VTE than healthy controls. The development of VTE in IBD seems to be multifactorial, resulting from multiple interactions between acquired and inherited risk factors. The most important independent acquired risk factors include disease activity, hospitalization, colonic localization, and recent surgery. The main genetic defects that have been established as risk factors for VTE in the general population are rather uncommon in IBD, but when present, they increase the risk of VTE. IBD has been demonstrated to represent an independent risk factor for the recurrence of VTE. An increased risk of VTE-related mortality when compared with non-IBD patients has been reported. The guidelines for diagnosis and treatment of IBD patients with VTE are similar to that of thrombotic non-IBD patients. There is a consensus on the use of thromboprophylaxis mainly in hospitalized IBD patients with acute flares, but the prevention strategies need further evaluation in future studies.
Keywords: Crohn disease; factor V Leiden; homocysteine; thromboembolism; ulcerative colitis